Association of ADIPOR2 gene variants with cardiovascular disease and type 2 diabetes risk in individuals with impaired glucose tolerance: the Finnish Diabetes Prevention Study - Eriksson Johan G; Schwab Ursula; Kolehmainen Marjukka; Lindström Jaana; Pulkkinen Leena; Siitonen Niina; Ilanne-Parikka Pirjo; Keinänen-Kiukaanniemi Sirkka; Tuomilehto Jaakko; Uusitupa Matti (Cardiovascular Diabetology, 2011)
Abstract Background Adiponectin is an adipokine with insulin-sensitising and anti-atherogenic effects. Two receptors for adiponectin, ADIPOR1 and ADIPOR2, have been characterized that mediate effects of adiponectin in various tissues. We examined whether genetic variation in ADIPOR2 predicts the development of cardiovascular disease (CVD) and/or Type 2 Diabetes (T2DM) in individuals with impaired glucose tolerance (IGT) participating the Finnish Diabetes Prevention Study (DPS). Methods CVD morbidity and mortality data were collected during a median follow-up of 10.2 years (range 1-13 years) and conversion from IGT to T2DM was assessed during a median follow-up of 7 years (range 1-11 years). Altogether eight SNPs in the ADIPOR2 locus were genotyped in 484 participants of the DPS. Moreover, the same SNPs were genotyped and the mRNA expression levels of ADIPOR2 were determined in peripheral blood mononuclear cells and subcutaneous adipose tissue samples derived from 56 individuals participating in the Genobin study. Results In the DPS population, four SNPs (rs10848554, rs11061937, rs1058322, rs16928751) were associated with CVD risk, and two remained significant (p = 0.014 for rs11061937 and p = 0.020 for rs1058322) when all four were included in the same multi-SNP model. Furthermore, the individuals homozygous for the rare minor alleles of rs11061946 and rs11061973 had increased risk of converting from IGT to T2DM. Allele-specific differences in the mRNA expression levels for the rs1058322 variant were seen in peripheral blood mononuclear cells derived from participants of the Genobin study. Conclusions Our results suggest that SNPs in the ADIPOR2 may modify the risk of CVD in individuals with IGT, possibly through alterations in the mRNA expression levels. In addition an independent genetic signal in ADIPOR2 locus may have an impact on the risk of developing T2DM in individuals with IGT. Trial registration number ClinicalTrials.gov NCT00518167